A RETROSPECTIVE STUDY ON ASSOCIATION/CORRELATION OF SERUM LACTATE LEVEL AT ADMISSION OF SEVERE PRE-ECLAMPSIA WITH MATERNAL COMPLICATIONS. - Akanksha Suman; Sangeeta Sinha (Student's Journal of Health Research, 2023)
Background This study aimed to determine whether severe pre-eclampsia is associated with an increased risk of birth-related complications based on serum lactate levels determined at hospital admission and to find potential markers that could be used to predict the occurrence of complications in pregnant women previously diagnosed with severe pre-eclampsia. Methodology Patients diagnosed with severe pre-eclampsia in the Indian state of Bihar between January 1, 2022, and December 31, 2022, were subjected to a retrospective analysis of hospital admission information. The patients who participated in this study were female. At the time of admittance, a record of the mother's difficulties and a serum lactate analysis were obtained. The nature of the relationship between maternal issues and serum lactate levels was investigated using statistical methods such as association and logistic regression. Results  Seventy-five percent of the 200 female participants in the study encountered at least one problem while hospitalized. 45% of the patients developed eclampsia, 32% developed acute renal impairment, and 24% developed disseminated intravascular coagulation. Serum lactate levels and obstetric complications were found to have a significant positive correlation (r = 0.72, p 0.001 for both statements). A logistic regression analysis revealed an association between an increased risk of maternal difficulties and a higher odds ratio per unit increase in lactate level of 1.58 (95% confidence interval: 1.31-1.80, p 0.001). Conclusion This study indicated severe pre-eclampsia admissions with high serum lactate levels were associated with maternal problems. Serum lactate levels may indicate complications in severe pre-eclampsia. Early detection of elevated lactate levels helps clinicians monitor high-risk patients for consequences. Recommendation Further prospective research is needed to confirm these findings and determine the best lactate threshold for predicting severe pre-eclampsia problems.